Representation of NCLB Implementation Program and Its Impact on Hispanic Students: A Critical Discourse Analysis on Media Reports - Riris Yusrina; Aris Munandar (Rubikon : Journal of Transnational American Studies, 2023)
No Child Left Behind (NCLB) aims to improve US education system. Every student in the US must have the same rights to get a quality education. The state is responsible for providing fair, equitable and quality educational facilities to the community. In reality, however, the NCLB was not entirely successful. While the law stipulates equality for underprivileged students, in reality, the richer students get better facilities and the best teachers. In addition, not all school teachers meet the standards. Based on these problems, this study aims to examine the challenges NCLB faced. It also intends to investigate the ideal implementation of NCLB and its effectiveness for students in the United States. This research also explores minority groups, like Hispanics. They are the largest minorities in the US. This research seeks to answer (1) How is the NCLB implementation reported in the media? and (2) What are the impacts of the NCLB implementation on Hispanic students?. This study uses the theory of Critical Discourse analysis from Norman Fairclough and Jager with news articles as data sources. The news articles were taken from the New York Times, usnews.com, dailynews.com, fivethirtyeight.com, and CBS News. The results found that the NCLB is still problematic that still there are achievement gaps, protests, and low performance. In addition, there are still wrong beliefs, discrimination, and dishonesty regarding the implementation of NCLB. Through some possible ways to solve the problem, like supervising and revising NCLB.